Literary literature in pedagogy courses: where is EJA? - Miguel, José Carlos [UNESP]; da Silva, Cláudio Rodrigues [UNESP]; Leal, Luciana Ferreira; Moraes, Agnes Iara Domingos (FapUNIFESP (SciELO), 2024)
This paper presents data from a documental and bibliographic study that analyzes the offering of specific courses related to literary literature in the field of youth and adult education (EJA) in the curricula of three public universities located in the states of Mato Grosso do Sul, Paraná and São Paulo. The courses do not present, in their Political-Pedagogical Projects, specific subjects whose titles refer directly or nominally to EJA or its target audience. The vast majority do not address the issue of young people and adults in the disciplines related to literary literature. This implies a gap in terms of literary literature in the training of pedagogues. Pedagogy, as far as teaching in school education is concerned, legally qualifies students to act also in EJA, which has curricular specificities, including in terms of contents and methodologies, due to the age groups covered by this modality.
Literatura literaria en los cursos de pedagogía: ¿dónde está la EJA?
Literatura literária em cursos de pedagogia: cadê a EJA?
Keywords: Adult Education; Educación de Jóvenes y Adultos; Educação de Jovens e Adultos; Formación de Lectores; Formación de Profesores; Formação de Leitores; Formação de Professores; Literary Literature; Literatura; Literatura Literária; Reader Training; Teacher Training; Youth